Reflections on the curriculum in internal medicine. - Veloso, A J (Acta Médica Portuguesa, 1993)
The author approaches the problem of postgraduate training in internal medicine. He points out that apart from the classic internist, one must consider the internist working in intensive care units or with special vocation in medical sub-specialties. He also approaches the relationship between internal medicine and medical sub-specialties as well as general practice, proposing a common trunk of two years for these branches of medical practice.